Front Cover. Issue 3 (2nd March 2021) - Memeo, Roberto; Paiè, Petra; Sala, Federico; Castriotta, Michele; Guercio, Chiara; Vaccari, Thomas; Osellame, Roberto; Bassi, Andrea; Bragheri, Francesca
Abstract: In our work we present an optofluidic‐based microscope on chip for 3D imaging of Drosophila embryos with dual color capabilities. The cover image shows the device during experimental validation along with the acquired images of two different embryos which are automatically optically sectioned while flowing in the microfluidic channel. The frames reveal internal volumetric features of the specimens. Further details can be found in the article by Roberto Memeo, Petra Paiè, Federico Sala, Michele Castriotta, Chiara Guercio, Thomas Vaccari, Roberto Osellame, Andrea Bassi, and Francesca Bragheri (e202000396 ). Abstract : In our work we present an optofluidic‐based microscope on chip for 3D imaging of Drosophila embryos with dual color capabilities. The cover image shows the device during experimental validation along with the acquired images of two different embryos which are automatically optically sectioned while flowing in the microfluidic channel. The frames reveal internal volumetric features of the specimens. Further details can be found in the article by Roberto Memeo, Petra Paiè, Federico Sala, Michele Castriotta, Chiara Guercio, Thomas Vaccari, Roberto Osellame, Andrea Bassi, and Francesca Bragheri (e202000396 ).